COVID-19 Mass Vaccination Campaign: An International Comparison of Qatar With GCC Nations and Other Global Groups - Yasmin Ali Morad Abdullahi (Frontiers Media S.A., 2023)
Objectives: Mass vaccination has been a key component in the effort to control the COVID-19 pandemic. Different countries have formulated their mass vaccination campaigns in different ways and with different priorities, with varying results. This study focuses on the case of Qatar in comparison with regional neighbors in the Gulf Cooperation Community (GCC) and with global benchmarks (G7 and OECD nations) in terms of the deployment of its mass vaccination program.Methods: Data on national vaccine administration and policy were obtained from Our World in Data and the Oxford COVID-19 Government Response Tracker for the period of 25 November 2020, when public vaccination first began to be implemented within the GCC, and June 2021, when Qatar's mass vaccination campaign concluded. Factors compared cross-nationally included the total number of vaccine doses administered, doses administered per 100 population, the time taken to reach certain vaccination thresholds (5, 10, 25, 50, and 100 doses per 100 population), and policy regarding administration to specific priority groups. Cumulative vaccination rates were also compared graphically by date.Results: A descriptive comparison of vaccination rates illustrated that there were similar aggregate patterns among the GCC, G7, and OECD groups of countries, and that there was a great deal of heterogeneity in the patterns of vaccination between countries within each of these groups. The mass vaccination program in Qatar outpaced the aggregate GCC, G7, and OECD groups.Conclusion: There were large between-country differences in the speed of mass vaccination progress which did not appear to be directly explained by national wealth. It is suggested that administrative and program management factors could account for some of these differences.